Integrating Entrepreneurship and Innovation Education into Higher Vocational Education Teaching Methods Based on Big Data Analysis. (12th August 2022) - Tan, Longyan; Du, Feng
Abstract : At present, IT plays an increasingly important role in promoting the various industries in society. Similarly, IT is inseparable from the application of IT. To this end, the article first expounds the important role that IT can play in providing a platform for IT, providing information support, and providing new opportunities in the colleges. Secondly, it points out that there are problems such as insufficient application, imperfect facilities, and one-sided application of IT in colleges. Finally, it discusses the establishment of an incentive mechanism for IT with it, the improvement of its facilities, the construction of an intelligent service system based on IT, and the construction of a virtual practice venue based on education. This paper puts forward the realization ways of IT in colleges.